The Influence of the Tahfidzul Qur’an Program and Learning Motivation on Academic Achievement - Fani Raihan Fadilah; Diana Ratna Sari; Suklani Suklani (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to gain a comprehensive understanding of empirical data regarding the relationship between the Tahfidzul Qur’an program and learning motivation, both individually and jointly, with the academic achievement of student cadres. The research is based on the assumption that learning the Qur’an, especially through memorization activities, not only improves students’ spiritual quality but also has the potential to enhance their motivation and performance in academic settings. The research hypotheses are: (1) There is a close and significant influence of the Tahfidzul Qur’an program toward students’ academic achievement; (2) There is a close and significant influence of learning motivation toward students’ academic achievement; and (3) There is a simultaneous influence between the Tahfidzul Qur’an program and learning motivation toward students’ academic achievement. To achieve the objectives of this study, the authors apply a survey method with a correlational approach aimed at identifying the extent to which the variables are related. The population consists of students who participate as cadres in the Tahfidzul Qur’an program. The research instruments used include observation to capture real conditions in the learning environment, interviews to obtain deeper qualitative insights, questionnaires to measure students’ motivation and participation level in the program, and documentary studies to collect relevant academic data. The data obtained are analyzed using correlation statistical analysis with the product moment correlation technique to determine the strength and significance of the relationships among variables. The findings of this study are expected to contribute to the development of educational strategies in integrating religious memorization programs with academic achievement improvement efforts.